CircHipk3 serves a dual role in macrophage pyroptosis by promoting NLRP3 transcription and inhibition of autophagy to induce abdominal aortic aneurysm formation - Donghua Cai; Chuling Li; Yingyuan Zhang; Sisi He; Yihai Guo; Wangjun Liao; Yulin Liao; Jianping Bin; Xiang He (Clinical and Translational Medicine)
Abstract Aims CircRNAs could regulate macrophage pyroptosis, which has the potential in promoting the synergistic effect of inflammation and matrix metalloproteinase (MMP) activity in abdominal aortic aneurysm (AAA). But the roles of circRNAs in modulating macrophage pyroptosis in the AAA remain unknown. This study explored the contribution to AAA of circHipk3, which was macrophage pyroptosis promoter, and the underlying mechanism. Methods and Results CircHipk3 was markedly upregulated in aortic aneurysms compared with that in normal arteries. In mice treated with circHipk3 contributed to macrophage pyroptosis, subsequently promoting the synergistic effect of inflammation and MMP synthesis, and significantly accelerated angiotensin (Ang) II‐ and porcine pancreatic elastase (PPE)‐induced AAA formation. Mechanically, chromatin isolation by RNA purification (ChIRP) indicated that circHipk3 facilitated macrophage pyroptosis by interaction with Stat3, increase the NLRP3 level in the aorta, and by binding Snd1 to promote Ptbp1 mRNA degradation to inhibit autophagy. Therefore, our study revealed the important role of circHipk3 in macrophage pyroptosis and thus significantly improved the outcome of AAA. Conclusions CircHipk3 serves a dual role in augmenting macrophage pyroptosis by interaction with Stat3, increase the NLRP3 level, and by binding Snd1 to promote Ptbp1 mRNA degradation to inhibit autophagy, thereby inducing aneurysm formation and progression. Key points CircHipk3 is significantly upregulated in abdominal aortic aneurysms (AAA) compared to normal arteries, contributing to macrophage pyroptosis. CircHipk3 promotes the synergistic effect of inflammation and matrix metalloproteinase (MMP) activity, accelerating Angiotensin II‐ and porcine pancreatic elastase‐induced AAA formation in mice. Mechanistically, CircHipk3 interacts with Stat3 to elevate NLRP3 levels and binds Snd1 to promote Ptbp1 mRNA degradation, inhibiting autophagy. CircHipk3's dual role in enhancing NLRP3 inflammasome activation and inhibiting autophagy makes it a critical regulator in AAA development and rupture. Targeting CircHipk3 may offer a novel therapeutic strategy to prevent pyroptosis and AAA development, positioning it as a potential treatment target.